Development and psychometric evaluation of the vaccine knowledge test for childhood vaccinations: using Rasch analysis - Deniz Kocoglu-Tanyer; Deniz S. Yorulmaz Demir (BMC Public Health)
Abstract Background There is a clear need for an up-to-date, comprehensive, and methodologically tested tool to assess parents’ knowledge of childhood immunization. The aim of this study was to develop a vaccine knowledge test for childhood immunization and to evaluate its validity and reliability. Methods This methodological study consists of three phases: creating an item pool, preparing a draft form, and psychometric evaluation. The draft form was developed with the help of a table of specifications and expert opinions. The psychometric assessment includes classical item analysis, Rasch analysis, KR-20, Cronbach’s alpha, and multiple regression analysis. Results The Vaccine Knowledge Test had an average item difficulty index of 0.498 and an average item discrimination index of 0.447. The WMS values of the items ranged from 0.81 to 1.14, and the UMS values ranged from 0.80 to 1.35, indicating good dispersion. The person separation index and the person number of strata of the Rasch analysis were 2.3 and 3.4. Cronbach’s alpha was 0.84. It was found that receiving vaccine education, having confidence in vaccines, being a parent, and having a university education were the determinants of vaccine knowledge, and these variables accounted for 29% of the variance in vaccine knowledge. Conclusion The Vaccine Knowledge Test, consisting of a single dimension and 28 items, is a valid and reliable measurement tool. It can reliably discriminate between individuals with different levels of knowledge or skills as low and high. It can be used as part of public health education and programs aimed at reducing vaccine hesitancy and preventing the destructive effects of vaccine misinformation in the community.